1993
DOI: 10.1111/j.1432-1033.1993.tb18064.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐dependent variation in the expression of elongation factor‐1α isoforms: Isolation and characterisation of a cDNA encoding a novel variant of human elongation‐factor 1α

Abstract: A novel isoform of human elongation factor‐1α (EF‐1α2) has been characterised. It shows a high similarity to other EF‐1α proteins, especially to a rat EF‐1α variant and it has all the characteristics of a functional EF‐1α protein. The pattern of expression of both EF‐1α2 and EF‐1α was analysed in different human tissues. This showed that the two proteins were differentially expressed, EF‐1α2 was expressed in brain, heart, skeletal muscle and in the transformed cell lines AMA and K14, but was undetectable in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
134
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(141 citation statements)
references
References 42 publications
5
134
0
Order By: Relevance
“…Expression of eEF1A2 is restricted to terminally differentiated cells of skeletal muscle, heart, and brain and dominates in the postnatal period (12). Loss of eEF1A2 expression because of mutation of the eEF1A2 gene in wasted (wst) mice results in progressive motor neuron degeneration, muscle atrophy, paralysis, and death within 30 days after birth (12)(13)(14). The neurodegenerative phenotype of wst mice is similar to that of Zpr1 Ϫ/ϩ mice (10) as well as mice with reduced expression of SMN (15,16).…”
mentioning
confidence: 71%
“…Expression of eEF1A2 is restricted to terminally differentiated cells of skeletal muscle, heart, and brain and dominates in the postnatal period (12). Loss of eEF1A2 expression because of mutation of the eEF1A2 gene in wasted (wst) mice results in progressive motor neuron degeneration, muscle atrophy, paralysis, and death within 30 days after birth (12)(13)(14). The neurodegenerative phenotype of wst mice is similar to that of Zpr1 Ϫ/ϩ mice (10) as well as mice with reduced expression of SMN (15,16).…”
mentioning
confidence: 71%
“…In humans, two EEF1A protein isoforms (EEF1A1 and EEF1A2), which have similar elongation activity, are known (17,18). thus, we evaluated the effect of tIm knockdown on protein biosynthesis.…”
Section: Mechanisms Involved In Pro-proliferative and Anti-apoptotic mentioning
confidence: 99%
“…In humans, zation; atm, ataxia telangiectasia mutated; aKt, v-akt murine thymoma viral oncogene homolog; cDna, complementary Dna; cheK1, checkpoint kinase 1; cheK2, checkpoint kinase 2; chX, cycloheximide; csnK1e, casein kinase 1ε; ctrl, negative control; Dna, deoxyribonucleic acid; eeF1a2, eukaryotic elongation factor 1a2; fw, forward; hBV, hepatitis B virus; hcV, hepatitis c virus; hcc, hepatocellular carcinoma; IP, immunoprecipitation; mDm2, mouse double minute homolog 2; mDm4, mouse double minute homolog 4; mtoR, mammalian target of rapamycin; nl, normal liver; oF, oligofectamine control; p21, cyclin-dependent kinase inhibitor 1a (cDKn1a, cip1); p53, tumor protein p53; PI3K, phosphoinositide-3-kinase; Page, polyacrylamide gel electro phoresis; PeR1, period circadian clock 1; PeR2, period circadian clock 2; Pt, peritumorous, non-neoplastic liver tissue; PUma, Bcl2 binding component 3; qRt-PcR, quantitative real-time polymerase chain reaction; Rna, ribonucleic acid; RoRa, RaR-related orphan receptor a; rev, reverse; sDs, sodium dodecyl sulfate; sem, standard error of the mean; sinc, non-target control siRna; siRna, short interfering Rna; sitIm, siRna targeting timeless; tIm, timeless; tIPIn, tImeless interacting protein; tma, tissue microarray; WB, western immunoblotting two EEF1A isoforms are known. while EEF1A1 is expressed in almost all tissues, EEF1A2 expression was only reported in heart, brain and skeletal muscle (17,18). however, eeF1a2 exerts an anti-apoptotic function, which may explain its role in tumorigenesis (19).…”
Section: Introductionmentioning
confidence: 99%
“…eEF1A1 is expressed ubiquitously, whereas eEF1A2 expression is restricted to the heart, the brain, and the skeletal muscles in humans and rodents. 16,17 It has been shown that increased expression of eEF1A1 and eEF1A2 proteins is associated with increased cell proliferation, oncogenic transformation, and delayed cell senescence. 14,18,19 It is interesting to note that cellular redistribution of eEF1A is related to pH i .…”
mentioning
confidence: 99%